Bioversity International – Impacts - Bioversity International (2012)
These are among the achievements Bioversity International has helped secure as the world’s only global non-profit research organization focused on agricultural biodiversity. It is our mission to research and promote the use and conservation of agricultural biodiversity, with our partners, in order to implement practical change and sustainability on the ground in areas hardest hit by poverty and where farmers need help most.Successes are many, achieved hand in hand with partners, and will continue to grow and evolve to meet the needs of the communities we serve.